Comparison of Metal Content of Coffee Samples Grown in Different Countries by Inductively Coupled Plasma Optical Emission Spectroscopy - Al-jaf, Sabah H.; Saydam, Sinan (My University, 2019)
Coffee is the one of the most consumed beverage across the world. Therefore, it has a commercial valueand social importance. Coffee consumption continues to increase due to its physiological effects, its pleasanttaste, aroma and many health benefits. In this study six different coffee samples from six different countrieswere analyzed for determining concentration of 17 elements by using inductively coupled plasma opticalemission spectroscopy (ICP-OES). According to the obtained results, elements were classified into threegroups of macro, micro, and trace elements according to their concentration; among the macro elementspotassium concentration were highest (10508 mg/L) average concentration in all samples; whereas theaverage concentration of calcium were found to be lowest (296.33 mg/L) in this group. Micro elementsshowed the concentration order of: Sr > Mn > Fe > Al > Ba > Cu > Zn by concentration of 12.66, 12.28,6.35, 3.81, 3.79, 3.05, and 2.61 mg/L respectively. Concentrations of selenium were higher than all otherelements in the group of trace elements by average concentration of 0.61 mg/L. The results obtained in thisstudy showed there are significant differences between different elemental content of different coffeesamples grown in different region.
Keywords: Kimya; Analitik; Spektroskopi